Re-establishing the South Central Farm: Community Organizing for Food Justice and Land Access in Los Angeles - Briseño, Miranda. (Tufts University. Tisch Library., 2021)
Thesis (M.A.)--Tufts University, 2021.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Julian Agyeman.; Committee: Penn Loh.; Keywords: Urban planning, Environmental justice, and Agriculture.